Llengua i literatura catalanes a la Catalunya del Nord (1883-1941). - FELIU, FRANCESC; FERRER, JOAN (Scripta)
The article "Catalan language and literature in Northern Catalonia (1883-1941)" analyzes the literary production in Catalan in the region between the late 19th and early 20th centuries. Estel Aguilar Miró studies the Renaixença in Rosselló, the Société d'Études Catalanes, the Colla del Rosselló, and Nostra Terra, highlighting figures such as Justí Pepratx and Joseph Baches. The work emphasizes the importance of Catalan literature in the cultural identity of the region.